Structural Changes and Microstructure of Maraging Steel Lattice Structures using Additive Manufacturing - Hanzl, Pavel; Zetková, Ivana; Kučerová, Ludmila (Manufacturing Technology Journal, 2019)
Direct Metal Laser Sintering (DMLS) is a method of additive manufacturing (AM), which builds metal parts in a layer by layer procedure based on a CAD template. The melting of metal powder by an energy beam and successful mastering of the whole manufacturing procedure requires complex management. Physical and chemical metallurgical phenomena occur during melting of the material and the final microstructure depends on many factors. This study investigates the microstructure of struts depending on their distance from the building platform. It is known that metal powder does not allow the dissipation of heat in the same way as molten material due to gas interstitial volume between the spherical particles. Metallography and micro-hardness were investigated on maraging steel 1.2709. Different melting strategies are recognizable in the macroscopic structure of metal alloys. Interesting facts have been discovered, for instance lose molten group or change of hardness depending on a shape of metal cells. In generally, significant differences were not found between individual specimens.
Keywords: Metal Additive Manufacturing; Cellular Lattice Structures; Metallography; Selective Laser Melting